Nabywanie kompetencji z zakresu języka polskiego przez dzieci przedszkolne w grupie wielojęzycznej = Acquisition of Polish language competences by preschool children in a multilingual group - Skrzetuska, Ewa; Majkowska, Małgorzata (Zielona Góra: Lubuskie Towarzystwo Naukowe)
The article deals with the language acquisition among children in a multicultural kindergarten. The aim of the research was to observe changes in the use of Polish vocabulary by four-year-old imigrant children. Observations focused on the manner of communication as well as kindergarten situations that enabled the children to expand their vocabulary. Word growth of six linguistically diverse immigrant children were examined.
Keywords: multiculturalism; kindergarten; language acquisition; wielokulturowość; przedszkole; nabywanie języka